Studies on the Zoarcidae (Teleostei: Perciformes) of the southern hemisphere. IX. A new species of Pachycara from the southwestern Atlantic - Anderson, M. E.; Mincarone, Michael M. (Zootaxa, 2006)
A new species of deep-sea eelpout, Pachycara alepidotum, is described from four specimens, 199– 282 mm SL, collected in the upper bathyal zone off Rio Grande do Sul state, southern Brazil, and is the first record of the genus in the southwestern Atlantic. It is characterized by its lack of scales and ventral lateral line, few caudal vertebrae and only 1–2 rakers on the upper limb of the first gill arch. The largest specimen is an adult female.